Perception, power, participation - Bianchizza, Chiara
The author explained how social and human resources have increased the resilience to climate change of vulnerable communities in Bangladesh. She described how non-government organizations work to build community capacity, and promotes approaches that give communities tools to identify issues and solutions themselves. She concluded by underlining the importance of strong social networks and gender equality in building capacity and securing resilience.